Acute exacerbation of chronic osteomyelitis triggered by aggravation of type 2 diabetes mellitus: a case report - Irie, Shintaro (J Med Case Rep, 2019)
BACKGROUND: Osteomyelitis is an infection in a bone. Acute osteomyelitis is observed mainly in the long leg bones of children and is usually treated with antibiotics. On the other hand, in adults, subacute or chronic osteomyelitis is more common. Antibiotics therapy is not necessarily effective for chronic osteomyelitis, and sometimes a surgical operation is performed for its remission. Furthermore, in classification of osteomyelitis by cause, type 2 diabetes mellitus is one of most common conditions associated with osteomyelitis. It isCase presentation well known that a variety of complications are induced in patients with type 2 diabetes mellitus due to chronic hyperglycemia, inflammatory reaction, and immunodeficiency, especially when glycemic control is poor. CASE PRESENTATION: A 58-year-old Japanese man had acute exacerbation of chronic osteomyelitis triggered by aggravation of type 2 diabetes mellitus. He had acute osteomyelitis in his right lower leg in his babyhood. After this episode, he did not experience any pain in his leg for approximately 50 years; he felt acute pain in his right lower leg at the age of 50 when his glycemic control was very poor. He then started undergoing medical therapy for type 2 diabetes mellitus and, after an improvement in glycemic control, his pain was gradually mitigated. However, he did not take medicine for approximately 8 months at the age of 58. After the interruption, glycemic control became very poor and he felt the similar acute pain again in the same area. After improving glycemic control, his pain was gradually mitigated again as observed at the age of 50. CONCLUSIONS: Here we report a case of chronic osteomyelitis under poorly controlled diabetic conditions. Interestingly, chronic osteomyelitis was observed at the same position where acute osteomyelitis was observed in his babyhood. In addition, chronic osteomyelitis was repeatedly observed, and it seemed that its acute exacerbation was closely associated with aggravation of type 2 diabetes mellitus. We should bear in mind that type 2 diabetes mellitus is one of the major risk factors of osteomyelitis and that acute exacerbation of chronic osteomyelitis could be triggered by a disturbance of glycemic control in patients with type 2 diabetes mellitus.